Effect Of Total Quality Management And Export Market Orientation On Export Performance Of The Furniture Industry In Jepara - Prasetya, Juliasari; Kristianto, Fesa Putra; Ma'rifah, Julia Dewi (At-Tadbir : jurnal ilmiah manajemen, 2025)
This study analyzes the moderating role of business network (BN) in the relationship between export market orientation (EMO), total quality management (TQM) and company export performance (CEP) in the furniture industry. Furniture industry selected as the focus of this research was located in Jepara. The research method used Partial Least Squares Structural Equation Modeling (PLS-SEM) technique involving 28 furniture industry company as samples. The result showed a significant relationship between EMO, TQM and CEP. Furthermore, it was found that BN plays an important moderating role in directing the relationship between EMO, TQM and CEP. These findings reveal that BN is not only a direct influencing variable, but also a key factor in enhancing the effectiveness of EMO and TQM, which in turn positively impacts CEP. This study made a valuable contribution to the literature and corporate practice by providing a better understanding of how EMO, TQM and BN processes can lead to more optimal export performance through EMO. The implications of this study can help firms in the Jepara furniture industry to improve their strategies, optimize business networks and achieve better export performance.